1991
DOI: 10.1002/aja.1001910307
|View full text |Cite
|
Sign up to set email alerts
|

Auditory epithelial migration. III. development of the stratified squamous epithelium of the tympanic membrane and external canal in the mouse

Abstract: The development of the stratified squamous epithelium of the tympanic membrane and external auditory canal was studied in serial sections of 124 mouse ears aged from 11 gestational days to 100 days. A fold developed from the edge of the fundus of the primary canal. It possessed two regions: firstly the meatal plate, which produced the pars tensa-covering epithelium (zone 2) and most of the deep ear canal epithelium (zone 3), and secondly the fundal extension plate, which grew from that part of the fundus not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Constraining the position of the daughter cells can have a strong effect on resulting mosaic pattern (6). For example, contact inhibition of division is important in organ patterning (7, 8). A testable prediction of the hypothesis that recursive and iterative stereotypical cell division rule sets regulate organ parenchyma development is that the resulting tissue will have a fractal geometry (1).…”
mentioning
confidence: 99%
“…Constraining the position of the daughter cells can have a strong effect on resulting mosaic pattern (6). For example, contact inhibition of division is important in organ patterning (7, 8). A testable prediction of the hypothesis that recursive and iterative stereotypical cell division rule sets regulate organ parenchyma development is that the resulting tissue will have a fractal geometry (1).…”
mentioning
confidence: 99%
“…Using confetti reporter mice, with the above cre lines in vivo, clonal units of keratinocytes were evident in the TM epidermis, streaking downwards from the malleolar folds over a 3‐month period (Frumm et al, ). This is in contrast to the radial movement seen in historic dye studies (Alberti, ; R. K. Jackler et al, ; L. Michaels & Soucek, ; Figure b), which may have been confounded by inadvertent injury with the placement of dye or may have been reflecting migration from committed progenitor zones, such as the manubrium. The authors pose the hypothesis that the area where the pars tensa and pars flaccida meet is a true stem cell niche, that is, the cells that maintain the TM epidermis reside in this area.…”
Section: Introductionmentioning
confidence: 66%
“…In contrast, the PT was morphologically quite differ ent from the EAC. However, it is still under consideration whether the HM region belongs to the superior part [9] or the inferior part. In a few mice, our preliminary study showed the finger-like projections not only in the annular region of the EAC but also in the HM region.…”
Section: Discussionmentioning
confidence: 99%
“…First, as demonstrated in an embryological study [9], the TM and EAC can be divided roughly into two parts: (1) the superior part, including the PF and the superior wall of the EAC, and (2) EAC. Our results also suggested a basis for this classsification.…”
Section: Discussionmentioning
confidence: 99%